LAYANAN BIMBINGAN KONSELING DI SEKOLAH DASAR - Dwikky Bagus Pangestu; Tri Umari; Elni Yakub (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Guidance and counselling services in elementary schools are important in the educational context. It is related to assisting the development task of independent, productive, and creative students. In elementary schools, most of the guidance and counselling services are carried out by the homeroom teacher which is implemented during the learning activity. Homeroom teachers in elementary schools applied guidance and counselling services including basic services, responsive services, individual planning, and system support in order to help, prevent, and overcome the problems faced by students. In fact, most of the guidance and counselling teachers have not been placed in elementary schools, as well as a special time for guidance and counselling services. It causes the implementation of guidance and counselling services not to run optimally. The research in this article is aimed to determine the implementation of guidance and counselling services applied by homeroom teachers through planning, implementing, and evaluating in Pekanbaru. The research sample was 30 homeroom teachers. In addition, a written interview measuring instrument and a guidance and counselling service scale were used in this research with instrument validity of 0.4 and reliability of 0.886. Data analysis was carried out by descriptive analysis test using the percentage formula. The results indicated that there was a homeroom teacher’s role in implementing guidance and counselling services through planning, implementation, and evaluation.